Economic-effective multi-energy management with voltage regulation networked with energy hubs - Zhao, Pengfei; Gu, Chenghong; Hu, Zechun; Zhang, Xin; Chen, Xinlei; Hernando-Gil, Ignacio; Ding, Yucheng (IEEE, 2020)
This paper develops a novel two-stage coordinated volt-pressure optimization (VPO) for integrated energy systems (IES) networked with energy hubs considering renewable energy sources. The promising power-to-gas (P2G) facilities are used for improving the interdependency of the IES. The proposed VPO contains the traditional volt-VAR optimization functionality to mitigate the voltage deviation while ensuring a satisfying gas quality due to the hydrogen mixture. In addition to the conventional voltage regulating devices, i.e., on-load tap changers and capacitor banks, P2G converter and gas storage are used to address the voltage fluctuation problem caused by renewable penetration. Moreover, an effective two-stage distributionally robust optimization (DRO) based on Wassersteain metric is utilized to capture the renewable uncertainty with tractable robust counterpart reformulations. The Wasserstein-metric based ambiguity set enables to provide additional flexibility hedging against renewable uncertainty. Extensive case studies are conducted in a modified IEEE 33-bus system connected with a 20-node gas system. The proposed VPO problem enables to provide a voltage-regulated economic operation scheme with gas quality ensured that contributes high-quality but low-cost multi-energy supply to customers.
Keywords: Distributionally robust optimization; energy hub; gas quality management; integrated energy system; two-stage framework